2007
DOI: 10.1128/jvi.01280-06
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Vaccinia Virus Challenge by CD8 Memory T Cells Resolved by Molecular Mimicry

Abstract: Live vaccinia virus (VV) vaccination has been highly successful in eradicating smallpox. However, the mechanisms of immunity involved in mediating this protective effect are still poorly understood, and the roles of CD8 T-cell responses in primary and secondary VV infections are not clearly identified. By applying the concept of molecular mimicry to identify potential CD8 T-cell epitopes that stimulate cross-reactive T cells specific to lymphocytic choriomeningitis virus (LCMV) and VV, we identified after scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 58 publications
(89 reference statements)
2
40
0
1
Order By: Relevance
“…LCMV and VACV share a complex matrix of CD8 T cell crossreactivity, which has been defined and studied molecularly. 28,52,57 Herein, adoptive transfer studies showed that T cell private specificity of crossreactive memory responses plays a major role in the protection and immunopathology. 32,33 The IAV+LCMV respiratory infection mouse model is noteworthy in that there are both higher titers of LCMV and much greater lung pathology in mice previously infected with IAV, both detrimental effects of heterologous immunity.…”
Section: Heterologous Immunity and T Cell Crossreactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…LCMV and VACV share a complex matrix of CD8 T cell crossreactivity, which has been defined and studied molecularly. 28,52,57 Herein, adoptive transfer studies showed that T cell private specificity of crossreactive memory responses plays a major role in the protection and immunopathology. 32,33 The IAV+LCMV respiratory infection mouse model is noteworthy in that there are both higher titers of LCMV and much greater lung pathology in mice previously infected with IAV, both detrimental effects of heterologous immunity.…”
Section: Heterologous Immunity and T Cell Crossreactivitymentioning
confidence: 99%
“…40,47 Clear networks of crossreactive epitopes and patterns of beneficial or detrimental heterologous immunity have been defined in specific virus sequences in mouse models (Supplementary Figure 1). [24][25][26][27][28][29][30][31][32][33][34][48][49][50][51][52][53] For example, in the C57BL/6 mouse (H2 b ), CD8 T cell crossreactive epitopes have been defined between LCMV and Pichinde virus (PICV), LCMV and vaccinia virus (VACV), LCMV and murine cytomegalovirus (MCMV), LCMV and IAV, IAV and MCMV, and PICV and VACV, and complex networks of mouse or human T cell crossreactivity can exist between two viruses. 23,24,27,28,34,[54][55][56] Furthermore, structural studies on crossreactivity between LCMV and VACV epitopes can pinpoint the target of crossreactivity and render the OVA SIINFEKL epitope crossreactive with LCMV by an amino acid substitution.…”
Section: Heterologous Immunity and T Cell Crossreactivitymentioning
confidence: 99%
“…BL/6 mice were infected intraperitoneally with a non-lethal dose of 5 ϫ 10 4 plaque-forming units of LCMV as previously described (25). Mice were considered immune at greater than 6 weeks after infection (9). Splenocytes from LCMV immune mice were co-cultured with mouse RMA cells that were pulsed with 1 M GP34 peptide, washed, and then ␥-irradiated (3000 rads) as previously described (9).…”
Section: Production Of Class I H-2kmentioning
confidence: 99%
“…Mice were considered immune at greater than 6 weeks after infection (9). Splenocytes from LCMV immune mice were co-cultured with mouse RMA cells that were pulsed with 1 M GP34 peptide, washed, and then ␥-irradiated (3000 rads) as previously described (9). RMA is a K b -positive, Rauscher virus-induced, T-lymphoma cell line of BL/6 origin.…”
Section: Production Of Class I H-2kmentioning
confidence: 99%
See 1 more Smart Citation